Freshwater and marine ecology - Sommer, Ulrich (Switzerland : Springer, 2023)
Freshwater and Marine Ecology is an introduction to the field of aquatic ecology, integrating the conceptually and methodologically widely overlapping fields of limnology and biological oceanography. It is structured like most textbooks of general ecology, leading from more elemental entities (individuals having to cope with their environment) to increasingly overarching entities, from populations over communities and ecosystems to the biogeochemistry of the entire planet and, finally, an overview over the major human impacts on the aquatic components of the earth system. The book provides examples for all major theoretical concepts of general ecology while the usual ecology textbooks have a strong terrestrial bias and rely only on few aquatic examples. This book takes the contrasting approach, motivated by the fact the fact that life originated from aquatic systems and that surface waters cover more than 70% of the Earth$1 (Bs surface. The choice of studies used as examples in Freshwater and Marine Ecology provides a balanced mix of freshwater and marine studies, of field observations, experimental and modeling studies. The readers are confronted with very recent work leading to the forefront of contemporaneous research but also with classic studies which laid the foundations of theory development in the field. s
includes Index
Freshwater and Marine Ecology is a comprehensive text ideally serving for undergraduate courses in biological oceanography, limnology, and ecology, but also for advanced students, teachers and scientists who had limited exposure to aquatic sciences and/or ecology during their studies.
Keywords: Interactions -- Biogeochemistry -- Ecophysiology -- Aquatic habitat